1982
DOI: 10.1111/j.1751-0813.1982.tb02712.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary haemorrhage in standardbred horses after racing

Abstract: Endoscopic examinations of the upper respiratory tract were done on 92 of 314 Standardbred horses that raced one or more times at 4 consecutive, weekly race meetings. Although participation was voluntary, the characteristics of the population of horses examined were not statistically different from those of all horses that raced. No horse showed epistaxis, but 34 (32.4%) examinations of the trachea revealed blood that ranged from a trace in the tracheal mucus to large amounts scattered over the tracheal walls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2
3

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 1 publication
1
12
2
3
Order By: Relevance
“…Frequency of epistaxis increased with the horse' s age, which was in agreement with findings of previous reports. 1,2,5,6,14 A relationship between sex and epistaxis was not detected by use of the χ 2 test in the present study; however, this factor was significant in the multiple logistic regression, which controlled for the other factors. Some previous studies have also indicated that the frequency of epistaxis or EIPH is higher in females than in males, 3,4 but others have not found such a relationship.…”
Section: Crude or Adjusted Orcontrasting
confidence: 69%
“…Frequency of epistaxis increased with the horse' s age, which was in agreement with findings of previous reports. 1,2,5,6,14 A relationship between sex and epistaxis was not detected by use of the χ 2 test in the present study; however, this factor was significant in the multiple logistic regression, which controlled for the other factors. Some previous studies have also indicated that the frequency of epistaxis or EIPH is higher in females than in males, 3,4 but others have not found such a relationship.…”
Section: Crude or Adjusted Orcontrasting
confidence: 69%
“…However, there are 2 studies that investigated an association between ambient temperature and EIPH in Standardbred racehorses. A study in Australia did not identify an association between EIPH and ambient temperature (9–22° C) in Standardbred horses (Speirs et al . 1982) whereas there was a significant correlation between the proportion of Standardbred horses with EIPH on a given day in Canada and the ambient temperature (‐15–25°C) (Lapointe et al .…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies of the risk factors for EIPH detected by endoscopic examination (Pascoe et al . 1981; Speirs et al . 1982; Raphel and Soma 1982; Lapointe et al .…”
Section: Introductionmentioning
confidence: 99%
“…Exercise-induced pulmonary haemorrhage (EIPH), the observation of blood in the large airways following intense exercise, occurs in many breeds of racing horses, including Thoroughbreds (Pascoe and Wheat 1980), Quarter Horses (Hillidge et al 1984), Appaloosas (Hillidge et al 1986), and Standardbreds (Pascoe and Wheat 1980;Speirs et al 1982;MacNamara et al 1990). The prevalence of EIPH revealed by a single endoscopic evaluation in Thoroughbreds has been shown to range from 42% (Pascoe and Wheat 1980) to 75% (Raphel and Soma 1982).…”
Section: Introductionmentioning
confidence: 99%